Readout‐Segmented Echo‐Planar Diffusion‐Weighted MR Imaging Improves the Differentiation of Breast Cancer Receptor Statuses Compared With Conventional Diffusion‐Weighted Imaging. Issue 3 (17th January 2022) - Zhong, Minghao; Yang, Zhiqi; Chen, Xiaofeng; Huang, Ruibin; Wang, Mengzhu; Fan, Weixiong; Dai, Zhuozhi; Chen, Xiangguang
Abstract : Background: Readout‐segmented echo‐planar diffusion‐weighted imaging (RS‐EPI) can improve image quality and signal‐to‐noise ratio, the resulting apparent diffusion coefficient (ADC) value acts as a more sensitive biomarker to characterize tumors. However, data regarding the differentiation of breast cancer (BC) receptor statuses using RS‐EPI are limited. Purpose: To determine whether RS‐EPI improves the differentiation of receptor statuses compared with conventional single‐shot (SS) EPI in breast MRI. Study Type: Retrospective. Population: A total of 151 BC women with the mean age of 50.6 years. Field strength/Sequence: A 3 T/ RS‐EPI and SS‐EPI. Assessment: The ADCs of the lesion and normal background tissue from the two sequences were collected by two radiologists with 15 years of experience working of breast MRI (M.H.Z. and X.F.C.), and a normalized ADC was calculated by dividing the mean ADC value of the lesion by the mean ADC value of the normal background tissue. Statistical Tests: Agreement between the ADC measurements from the two sequences was assessed using the Pearson correlation coefficient and Bland–Altman plots. One‐way analysis of variance, Kruskal–Wallis test, and median difference were used to compare the ADC measurements for all lesions and different receptor statuses. A P value less than 0.05 indicated a significant result. Results: The ADC measurements of all lesions and normal background tissues were significantly higher on RS‐EPI than on SS‐EPI (1.82 ± 0.33 vs. 1.55 ± 0.30 and 0.83 ± 0.11 vs. 0.79 ± 0.10). The normalized ADC was lower on RS‐EPI than on SS‐EPI (0.47 ± 0.11 vs. 0.53 ± 0.12, a median difference of −0.04 [95% CI: −0.256 to 0.111]). For both diffusion methods, only the ADC measurement of RS‐EPI was higher for human epidermal growth factor receptor‐2 (HER‐2)‐positive tumors than for HER‐2‐negative tumors (0.87 ± 0.10 vs. 0.81 ± 0.11), and this measurement was associated with HER‐2 positive status (adjusted odds ratio [OR] = 654.4); however, similar results were not observed for the ADC measurement of SS‐EPI (0.80 ± 0.10 vs. 0.78 ± 0.11 with P = 0.199 and adjusted OR = 0.21 with P = 0.464, respectively). Data Conclusion: RS‐EPI can improve the distinction between HER‐2‐positive and HER‐2‐negative breast cancer, complementing the clinical application of diffusion imaging. Evidence Level: 3 Technical Efficacy: Stage 1